Bmx regulates LPS-induced IL-6 and VEGF production via mRNA stability in rheumatoid synovial fibroblasts. - Palmer, C; Mutch, B; Page, T; Horwood, N; Foxwell, B (2008)
Discordant cytokine production is characteristic of chronic inflammatory conditions like rheumatoid arthritis (RA), and anti-cytokine therapeutics are becoming routinely used to treat RA in the clinic. Fibroblasts from rheumatoid synovium have been shown to contribute to cytokine production in inflamed joints; likewise these cells also produce cytokines in response to inflammatory mediators signalling through Toll like receptors (TLRs). Tyrosine kinase activity is essential to LPS-induced cytokine production, and we have previously implicated a role for the Tec kinase, Bmx, in inflammatory cytokine production. Here we show that Bmx kinase activity in RASF is increased following LPS stimulation and that Bmx is involved in the regulation of LPS-induced IL-6 and VEGF production via mRNA stabilisation. This is an important insight into the regulation of VEGF, which is involved in a wide range of different pathologies, and may lead to more effective design of novel anti-inflammatory/angiogenic therapeutics for conditions such as RA.